A Summary of “Die Wiedergutmachung nationalsozialistischen Unrechts durch die Bundesrepublik Deutschland Band V – Das Bundesentschädigungsgesetz Zweiter Teil” - Hagjija-Alaoui, Hanin; Justus Liebig University Giessen (My University, 2024)
The following article provides a brief summary of the fifth volume of the series “Die Wiedergutmachung nationalsozialistischen Unrechts durch die Bundesrepublik Deutschland” published, among others, by the Federal Ministry of Finance in six volumes, and is accordingly focused on those parts of the Federal Compensation Act which address financial losses.
Keywords: ddc:340